MODEL OF PRACTICAL PURPOSE TRAINING OF PRIMARY SCHOOL TEACHERS-TO-BE TO GET THEM READY TO USE CULTURAL COMPETENCE IN THEIR PROFESSIONAL ACTIVITIES - Hrechanyk, N.I (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2020)
The purpose of this study is to test the effectiveness of the model of practical purpose training of primary school teachers-to-be to get them ready to use cultural competence in their professional activities, and the was to study the impact of the model on such structural components of the above competence, in accordance with the Pedagogical Constitution of Europe, which are as follows: socio-cultural mobility, leadership, empathy, intercultural tolerance and socio-cultural awareness, which were decided to be variables within the flow of the experimental model testing. Diagnostic tests and checklists were used to collect statistics, namely: Fan and Mak's Social Self-efficacy Scale; Situational scale of social avoidance; Interpersonal skills checklists; The Basic Empathy Scale in Adults; Cultural Competence Self-Assessment Checklist; Express leadership test; diagnostics of the level of formation of intercultural tolerance, intended to assess the levels of formation of these components at the pre-experimental and post-experimental stages. The Chi-Square statistical method and STATA Software were used to analyze the quantitative data that were summarized, converted into percentages and calculated. A training sessions-based model is capable to enhance students' sociocultural knowledge, their sociocultural mobility and leadership skills, improving their ability to manage their empathy and intercultural tolerance is effective, as it aims to build cultural competence as a specific model of adaptive behaviour, applied by future primary school teachers in their professional activities. This study deepens the study of the theory and methodology of forming cultural competence and the development of tools for assessing the formation of the cultural competence. The prospects for further research in this area can be seen in the substantiation of pedagogical conditions for the implementation of the methodological system of formation of cultural competence of future primary school teachers in the process of vocational training.